ANTARA IDEALITAS DAN REALITAS: EVALUASI KINERJA DPRD KOTA TASIKMALAYA DALAM PENGAWASAN ANGGARAN DAERAH PERSPEKTIF ISLAMIC GOVERNANCE - Ihsan Robbani, Muhammad; Noor, Fauz; fauz (Siyasyatuna | Jurnal Hukum Tata Negara, 2025)
This research aims to analyze the role of the Regional House of Representatives (DPRD) of Tasikmalaya City in supervising regional expenditure budgets from the perspective of siyasah syar'iyyah. Using a qualitative approach, data was collected through interviews, observations, and document studies. The research findings indicate that DPRD Tasikmalaya City has a strategic role in budget allocation, however, the implementation of supervisory functions still faces various challenges, such as limited capacity of DPRD members, lack of information transparency, and political intervention. According to the siyasah syar'iyyah perspective, supervision must adhere to the principles of justice, trustworthiness, and public welfare. This research recommends enhancing the capacity of DPRD members, strengthening supervisory mechanisms, and involving the community in the supervision process. With these measures, DPRD can be more effective in carrying out its supervisory functions and realizing good governance